2016
DOI: 10.1007/s11695-016-2307-9
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Balloon for Management of Severe Obesity: a Systematic Review

Abstract: Older models of intragastric balloons (IGBs) had unacceptably high complication rates and inconsequential weight loss. With FDA approval of newer models, we aimed to systematically examine the literature regarding the efficacy of IGB therapy for obesity. A comprehensive electronic database search was completed. Title searching was restricted to the following keywords: bariatric, gastric, gastric bypass, gastric band, sleeve gastrectomy, and intragastric balloon. Twenty-six primary studies (n = 6101) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
58
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 42 publications
3
58
0
6
Order By: Relevance
“…Most of the literature on the safety of IGBs focuses on the Bioenterics Intragastric Balloon (BIB; Apollo Endosurgery), which is marketed as the Orbera system in the US. Multiple meta‐analyses have been published since BIB inception, with consolidated data of complication rates, which are overall low and tend to be mild in nature . Early complications of BIB placement caused by the space‐occupying nature of the balloon include abdominal pain, nausea, vomiting, heartburn, and dyspepsia.…”
Section: Space‐occupying Therapiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the literature on the safety of IGBs focuses on the Bioenterics Intragastric Balloon (BIB; Apollo Endosurgery), which is marketed as the Orbera system in the US. Multiple meta‐analyses have been published since BIB inception, with consolidated data of complication rates, which are overall low and tend to be mild in nature . Early complications of BIB placement caused by the space‐occupying nature of the balloon include abdominal pain, nausea, vomiting, heartburn, and dyspepsia.…”
Section: Space‐occupying Therapiesmentioning
confidence: 99%
“…Early complications of BIB placement caused by the space‐occupying nature of the balloon include abdominal pain, nausea, vomiting, heartburn, and dyspepsia. In a systematic review of 26 studies (n = 6101) published between 1946 and 2015, it was found that as many as 23.3% of patients experienced nausea and vomiting and 19.9% of patients experienced abdominal pain . Yet another systematic review reported that abdominal pain and nausea occurred in 33.7% and 29% of subjects after Orbera implantation, respectively .…”
Section: Space‐occupying Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…
Dear editor, Please consider these comments in response to the Letter to the Editor submission raising concerns about our recently published article by Yorke et al, BIntragastric balloon for management of severe obesity: a systematic review [1].Ŵ e appreciate the interest taken to our article and acknowledge the peer-reviewed critique. Our paper reflects the issue of bridging morbidly obese patients to definitive bariatric surgery with the placement of intragastric balloons (IGB).
…”
mentioning
confidence: 99%